Implantation of Liquid Nitrogen Frozen Tumor Tissue after Posterior Decompression and Stabilization for Metastatic Spinal Tumors - Shinmura, Kazuya (Asian Spine J, 2015)
STUDY DESIGN: A retrospective study. PURPOSE: To evaluate the immunity-enhancing effect of implantation of a liquid nitrogen-treated tumor. OVERVIEW OF LITERATURE: We have developed a new technique of implanting a tumor frozen in liquid nitrogen after posterior decompression and stabilization, with the aim of enhancing antitumor immunity in order to prolong the survival period of the patient. In the current study, the immunity-enhancing effect of this new technique has been evaluated. METHODS: The subjects were 19 patients in whom we had earlier performed decompression and stabilization between April 2011 and September 2013. The 19 subjects were divided into two groups, namely a frozen autologous tumor tissue implantation group (n=15; "implantation group"), which consisted of patients, who underwent implantation with autologous tumor tissue frozen in liquid nitrogen, and a control group (n=4), which consisted of patients, who did not undergo autologous cancer transplantation. To evaluate the immunity-enhancing effect of the protocol, plasma cytokines (interferon [IFN]-γ and interleukin [IL]-12) were analyzed before surgery and a month after surgery. RESULTS: The mean rate of increase in IFN-γ was significantly higher in the implantation group (p=0.03). Regarding IL-12, no significant difference was observed between the groups, although the implantation group exhibited increased levels of IL-12 (p=0.22). CONCLUSIONS: Decompression and stabilization combined with autologous frozen tumor cell implantation can enhance cancer immunity in metastatic spinal tumor patients. It is hypothesized that this procedure might prevent local recurrence and prolong survival period.